Digital Government Readiness Assessment Toolkit : Guidelines for Task Teams - World Bank (World Bank, Washington, DC, 2020)
The Digital Government Readiness Assessment (DGRA) Toolkit is a knowledge product developed as a global public good to help client countries leaders in digital agenda and Information and Communication Technologies (ICT) sector assess their current status, as well as their aspirations in digital development of the country and transformation of the public sector by leveraging digital solutions.